IMPLEMENTING SIM-OVG MODEL IN LEARNING ECONOMICS AT SMA NEGERI 10 SAMARINDA - Watini Watini (Universitas Muhammadiyah Kalimantan Timur, 2019)
The reason underlying the implementation of the present study was because there was a finding revealing that there were still several students from cross-economics class of XI MIPA having difficulties in understanding the lessons. In addition, the students also had a kind of thought that economics was just about memorizing things which was not interesting and challenging that resulted in their unsatisfied learning outcomes. Therefore, the SIM-OVG model needed to be implemented in the learning process. The instruments of the present study were observation and, students’ learning reports and work method. The population of the study was the second grade students (4 classes) who enrolled economics subject at SMA Negeri 10 Samarinda, whereas the samples of the study were the students of XI MIPA-1 class (cross-economics class) at SMA Negeri 10 Samarinda. The number of the population and samples was 101 and 23 students respectively. The study lasted for one semester. The description of the classroom observation, the students’ scores and the group presentation were obtained for the data analysis. After implementing the SIM-OVG model, the results showed that; 1) in the affective aspect, the students showed a better attitude, 2) in the cognitive aspect, there was an improvement on the students’ learning outcomes (before the implementation of SIM-OVG model in XI MIPA-1 class, 52,17% of the students did not reach the passing-grade, but after the implementation, 100% of the students reached the passing-grade, and they also looked enthusiastic in doing their assignments, and 3) in the psychomotor aspect, the students became more skillful, creative, and be able to perform high level thinking. The researcher suggested that the dissemination should be done through MGMP forum and SIM-OVG model workshop. In addition, the researcher also suggested the integration of SIM-OVG model with other learning models and hoped that every school provided adequate facilities to support the implementation of SIM-OVG model.